2003
DOI: 10.5195/jwsr.2003.237
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing and Rethinking Linkages Between the Natural Environment and the Modern World-System: Deforestation in the Late 20th Century

Abstract: Building on prior work in world-system analysis and human ecology, we test a macro-level theory that social and demographic causes of deforestation will vary across zones of the modern world-system. Using multivariate regression analysis, we examine models of deforestation over the period 1990-2000. We test for main effects of world-system posmon, two different population variables (urbanization and proportion under working age), and economic development within zone, as well as for the contextual effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
173
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(187 citation statements)
references
References 112 publications
9
173
4
1
Order By: Relevance
“…However, this capacity has not always been supported empirically; in the case of deforestation, semi-peripheral countries have experienced higher rates of deforestation than those at the periphery, likely attributed to a historical artifact, whereby peripheral countries were yet to experience similar levels of urbanization (Burns et al 1997;Burns 2003 et al;Jorgenson 2004). Studies have found that such relationships may vary by pollutant; for example, greenhouse gas emissions are linearly related to position in the world system hierarchy, whereas methane emissions tend to be heaviest in semi-peripheral countries (Burns et al 1997;Jorgenson 2004).…”
Section: Ecologically Unequal Exchange As a Political Lensmentioning
confidence: 99%
“…However, this capacity has not always been supported empirically; in the case of deforestation, semi-peripheral countries have experienced higher rates of deforestation than those at the periphery, likely attributed to a historical artifact, whereby peripheral countries were yet to experience similar levels of urbanization (Burns et al 1997;Burns 2003 et al;Jorgenson 2004). Studies have found that such relationships may vary by pollutant; for example, greenhouse gas emissions are linearly related to position in the world system hierarchy, whereas methane emissions tend to be heaviest in semi-peripheral countries (Burns et al 1997;Jorgenson 2004).…”
Section: Ecologically Unequal Exchange As a Political Lensmentioning
confidence: 99%
“…Jorgenson (2006) argues that poor nations largely rely on export markets to stimulate economic growth. In this regard, nations often export primary products and agricultural goods, which increase deforestation (Burns et al 2003). However, forest loss may be mitigated to the extent that nations have something other than raw materials to export like services and manufactured goods.…”
Section: 968mentioning
confidence: 99%
“…Moreover, low levels of economic activity and the fiscal austerity associated with large foreign debts prevent the creation of jobs in sectors other than agriculture that otherwise might attract people to cities and relieve the human demand on forest resources (Burns, Kick, and Davis 2003). The absence of alternative economic opportunities and the increase in the number of people competing for these opportunities compel individuals to expand agricultural production by clearing forests (Burns et al 2003). This often occurs when an "army of surplus laborers" moves to obtain property by clearing land when road building opens up a region for development (Rudel 1993).…”
Section: Neo-malthusian Theorymentioning
confidence: 99%
“…Since the 1997 American Sociological Association -Political Economy of the World-System (PEWS) section meeting, PEWS authors addressing environmental issues (Bunker and Ciccantell 2005;Moore 2003;Prew 2003) have built on the initial contributions of Braudel (1979a;1979b;1979c), Wallerstein (1974;1980;1989) and Bunker (1985), as well other researchers who have expanded on their own and others' formulations (Burns, Kick, and Davis 2003;Grimes and Kentor 2003;Jorgenson 2003;Roberts, Grimes, and Manale 2003). Previous studies have established a connection between the position in the world-economy and their environmental impact and have added greatly to our understanding of the issue (Burns, Davis, and Kick 1997;Burns, et al 2003;Burns, Kick, Murray, and Murray 1994;Jorgenson 2003;Jorgenson 2006;Jorgenson, Rice, and Crowe 2005;Roberts 1996;Roberts, et al 2003;York, Rosa, and Dietz 2003).…”
Section: Introductionmentioning
confidence: 99%